Clonal spread of carbapenem-resistant Klebsiella pneumoniae among patients at admission and discharge at a Vietnamese neonatal intensive care unit - Björn Berglund (BMC, 2021)
Abstract Background The increasing prevalence of carbapenem-resistant Enterobacteriaceae (CRE) is a growing problem globally, particularly in low- to middle-income countries (LMICs). Previous studies have shown high rates of CRE colonisation among patients at hospitals in LMICs, with increased risk of hospital-acquired infections. Methods We isolated carbapenem-resistant Klebsiella pneumoniae (CRKP) from faecal samples collected in 2017 from patients at admission and discharge at a Vietnamese neonatal intensive care unit (NICU). 126 CRKP were whole-genome sequenced. The phylogenetic relationship between the isolates and between clinical CRKP isolates collected in 2012–2018 at the same hospital were investigated. Results NDM-type carbapenemase-(61%) and KPC-2-encoding genes (41%) were the most common carbapenem resistance genes observed among the admission and discharge isolates. Most isolates (56%) belonged to three distinct clonal clusters of ST15, carrying bla KPC-2, bla NDM-1 and bla NDM-4, respectively. Each cluster also comprised clinical isolates from blood collected at the study hospital. The most dominant ST15 clone was shown to be related to isolates collected from the same hospital as far back as in 2012. Conclusions Highly resistant CRKP were found colonising admission and discharge patients at a Vietnamese NICU, emphasising the importance of continued monitoring. Whole-genome sequencing revealed a population of CRKP consisting mostly of ST15 isolates in three clonally related clusters, each related to blood isolates collected from the same hospital. Furthermore, clinical isolates collected from previous years (dating back to 2012) were shown to likely be clonally descended from ST15 isolates in the largest cluster, suggesting a successful hospital strain which can colonise inpatients.